Effect of zinc particle shape on the anticorrosion properties of organic coatings containing zinc and a conductive polymer - Kohl, Miroslav; Kalendová, Andréa (CHEMagazín, s.r.o., 2016)
The aim of this work was to prepare organic coatings containing a conductive polymer and either spherical or lamellar zinc particles and to evaluate their mechanical and corrosion resistance. Polyaniline phosphate was used as the conductive polymer. This substance was prepared by oxidative polymerisation of aniline in 1 M phosphoric acid using ammonium peroxodisulphate as the oxidant. The oil number and density were determined for the pigment and the critical pigment volume concentration was calculated by using the data. Once the basic characteristics of the pigment had been established, the organic coatings were formulated. The organic coatings contained polyaniline phosphate at pigment volume concentrations 1%, 5% and 10%, to which zinc – spherical in one concentration series and lamellar in another series – had been added in amounts such that the total pigment volume concentration was constant and equal to the critical pigment volume concentration. The organic coatings were subjected to mechanical and corrosion tests. Mechanical tests included the impact test, bending test, cupping test and adhesion test. Corrosion was assessed in an accelerated cyclic test in salt spray atmosphere.
Vliv tvaru zinkových částic na korozní vlastnosti organických povlaků obsahujících vodivý polymer
Keywords: spherical zinc; lamellar zinc; conductive polymer; polyaniline; coating; sférický zinek; lamelární zinek; vodivý polymer; polyanilin; povlak